Ecstasy Unlimited : On Sex, Capital, Gender, and Aesthetics - Kipnis, Laura (Book collections on Project MUSE., 1993)
A unique collection of essays on popular culture, politics, aesthetics, feminism, and postmodernism, along with complete scripts from three of Kipnis' videotapes.